(untitled) (Journal of Economic Research & Business Administration, 2016)
Improving the state of public financing at the level of the republic and the region are poorly understood and require further study. The foregoing predetermined the choice of theme, purpose and objectives of the study and led to the need for comprehensive research of agricultural financing problems. In the context of the country’s entry into the Foreign Trade Organization of the state and sources of public financial support for agricultural producers, which can effectively and efficiently use financial resources they have been investigated and analyzed. Directions of perfection of process of formation of agricultural incomes should consist of a system of state regulation measures. One of the main industries of national economy complex economy is the agriculture of Kazakhstan. Here available products, it is vitally important for the whole society, along with that have accumulated a certain economic, resource and finansowy potential. The resource potential offered in the form of material and labor resources.